Preparation of new polyorganosiloxane acrylate and the properties of UV-cured acrylate compositions containing it - Liu, H.; Chen, M.; Xu, K.; Wang, Z. (Polimery, 2022)
A new polyorganosiloxane acrylate (POSA) has been obtained as a result of Michael addition reaction of polyorganosiloxane modified with cyclohexylamine with methyl end groups (MCAPS) and hexanediol diacrylate (HDDA). 1H NMR and FT-IR methods confirmed the course of a reaction of N-H groups of MCAMPS with acrylic groups of HDDA. POSA has been used to modification of UV-cured epoxy-acrylic system (HDDA + butyl acrylate + epoxy-diacrylate resin). It has been stated that even small POSA content (1-1.5 wt. %) causes significant changes of surface properties of cured coatings. Namely, contact angle and its hysteresis increase, gloss decreases while final hardness does not change. Using XDS method it was showed that POSA selectively concentrated on the surface of cured coatings.